Diagnostic Accuracy of Fine Needle Aspiration Cytology in Parotid Lesions. (31st May 2011) - Ali, Naeem Sultan; Akhtar, Shabbir; Junaid, Montasir; Awan, Sohail; Aftab, Kanwal
Abstract : Objective. Histopathology of parotid gland tumors is extremely varied and complex due to heterogeneous cellular composition. Preoperative diagnostic tools include fine needle aspiration cytology, the role of which remains controversial. The aim of this paper is to evaluate the usefulness and accuracy of fine needle aspiration cytology (FNAC) in the diagnosis of parotid gland tumors. Methods. We retrospectively reviewed charts of 129 patients who underwent parotidectomy for parotid lesions at Aga Khan University Hospital from 2002 to 2010. We compared the results of preoperative FNAC with final histopathological diagnosis. Results. Concordance with histological results was observed in 86%, specificity was 98%, sensitivity was 84%, and diagnostic accuracy was 94%. Conclusion. Our results demonstrate that preoperative cytology in parotid lesions is fairly accurate and useful in diagnosing benign from malignant and in planning appropriate approach for treatment.